Pengaruh Latihan Daya Tahan Terhadap VO2max Atlet Futsal MAN 1 Dharmasraya - Harika Fitri, Alchonity; Ricky, Zuhar (INSPIREE: Indonesian Sport Innovation Review, 2021)
The  purpose  of  the study. Physical conditions in futsal games will certainly affect the quality of passing, control, and technique and play on the field. Increasing the intensity of exercise and regulating the life pattern of athletes is the best solution for maintaining the athlete's endurance. This study aims to determine the effect of endurance training on the VO2Max results of the futsal athletes of MAN 1 Dharmasraya in 2020. Materials and methods. This research is an experimental research with one group pretest and posttest design. This research was conducted at the MAN 1 Dharmasraya school. The population in this study were all futsal athletes at MAN 1 Dharmasraya, totaling 9 people who were the research subjects. Data collection techniques, namely by observation, tests and measurements. The instrument used was a multi-stage test or bleep test. The data analysis used t-test at a significance level of 5%. Results. The highest increase in VO2Max level was achieved by Dipalpa Rego athletes with a change of 5.2 and the lowest change was athlete Hendri Pison F with a change of 3.4. The results of the percentage calculation showed that the increase in VO2Max of futsal athletes was 24.925%. Conclusions. Based on the results of the research and data analysis, it was concluded that there was an effect of endurance training on the VO2Max results of the futsal athletes of  MAN 1 Dharmasraya in 2020